The diagnosis and treatment of lower urinary tract dysfunction in children: a clinical perspective - Sarma, Vivek Parameswara; S., Aravind C. (International Journal of Contemporary Pediatrics, 2025)
The abnormalities in the filling and/or emptying phases of the bladder, with no obvious anatomical or neurological abnormality are considered as Functional disorders of the lower urinary tract (LUT). The term lower urinary tract dysfunction (LUTD) includes a wide spectrum of disorders with variable clinical presentation. LUTD is a common problem seen in daily practice that accounts for up to 40% of paediatric urology clinic visits in a year. The fact that it has been reported to affect 5–20% of all children highlights the clinical significance of this disorder. A thorough literature review of the studies, recommendations and practice guidelines of LUTD in children was done based on the clinical experience of the management of these children over the past decades. All the currently relevant information was summarized under the specific headings pertaining to diagnosis, classification and therapy. Any functional disturbance in voiding (abnormal holding and/or voiding pattern) that occurs beyond the expected age of completion of toilet training, in the absence of anatomical or neurological causes, is considered a Voiding disorder. LUTD include a wide spectrum of clinical entities that inhibit the development of normal urinary control and originate from behavioural factors that affect toilet training. LUTD is often associated with functional constipation and emotional/behavioural disorders. LUTD can lead to vesicoureteral reflux (VUR) and recurrent urinary tract infections (UTIs) with a significant risk of progressive renal scarring. The evolution of the understanding of the physiological basis of these disorders, aetiological factors, clarity in nomenclature and categorisation and advances in functional assessment have enabled the prospect of more definitive diagnosis and better therapy. Greater insight into the correlation of the findings of functional studies with specific disorders have facilitated more scientific and targeted therapy. The recognition of the importance of treatment of underlying factors and the use of escalating treatment protocols involving multiple specialists have aided to develop a more holistic and comprehensive therapeutic regime.